VERBALIZATION OF OPPOSITE CONCEPTS IN SYNTACTIC ANTONYMS - Sayidiraximova, Nasiba (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
Modern linguistics allows us to look at language phenomena from a completely different perspective. The reason is that any language and speech phenomena are analyzed together with the human factor. Such an anthropocentric paradigm approach to language phenomena makes it more urgent to re-examine the issues studied so far because such an approach has been achieved in the science of linguistics, expands the achievements, and fills them with completely different scientific conclusions. It is known that the phenomena of synonymy, antonymy, and homonymy in linguistics are applied in science - they are widely analyzed from the point of view of historical-typological, formal-structural, and systemstructural linguistics; in this regard, many scientific studies were conducted, monographs were created. However, these phenomena have not been sufficiently studied in the above-mentioned new - anthropocentric paradigm. In our opinion, such an approach further expands the terminological apparatus of these issues. For this, it is very important to analyze these events together with the human factor. It is known that the laws of dialectics are universal and specific, that the categories of necessity and chance, cause and effect themselves show the essence of the main contradiction and at the same time express mutual generality even when they are considered as separate categories.
Keywords: anthropocentric paradigm; cognitive linguistics; extralinguistic factors; the issue of the cognitive potential of antonyms; the possibilities of antonyms to create contrast; the realization of the principle of contrast